SELF-EFFICACY AS CORRELATES OF SECONDARY STUDENTS’ ACADEMIC ACHIEVEMENT IN MATHEMATICS IN OGIDI EDUCATION ZONE. (UNIZIK Journal of STM Education, 2026)
The study examined self-efficacy as correlates of students’ academic achievement in Mathematics in Ogidi Education Zone of Anambra state. Two research questions guided the study while two hypotheses were tested at 0.05 alpha level. A correlational survey design was adopted. The population of the study comprised 2,840 senior secondary school senior secondary two (SS2) Mathematics students from Ogidi Education Zone of Anambra state. The sample size of this study consists of 1,420 SS2 students offering Mathematics and drawn from secondary schools in Ogidi education zone, using multi stage sampling procedure. The instruments are Mathematics selfefficacy Questionnaire (MSEQ) and average termly score of from teacher’s grade book. The instrument used was validated by three experts, all from Nnamdi Azikiwe University, Awka. The reliability of the instruments was established using Cronbach alpha method. The reliability coefficients of MSEQ was found to be 0.85. The data were collected with the help of the research assistants who were Mathematics teachers. Pearson product moment correlation (r) and R2 were used to answer the research questions and to test the hypotheses. While Hayas process was use to answer research question and test hypotheses that has gender as moderating variable. The finding revealed that the relationship between self-efficacy and students’ academic achievement in Mathematics is moderately positive and not significant. Also the study found that the relationship between self-efficacy and students’ academic achievement in Mathematics as moderated by gender is moderately positive and significant. It was recommended that teachers should help students build self-confidence in Mathematics through regular practice, clear examples, and step-by-step feedback. Finally, Guidance counselors and class teachers should monitor students who show low confidence and offer support early, since self-efficacy showed at least moderately positive result
Keywords: Gender moderation, Mathematics achievement Self-efficacy.